The causal relationship between gut microbiota and nine infectious diseases: a two-sample Mendelian randomization analysis - Wang, Song; Yin, Fangxu; Sun, Wei; Li, Rui; Guo, Zheng; Wang, Yuchao; Zhang, Yiyuan; Sun, Chao; Sun, Daqing (Frontiers in Immunology, 2024)
Background: Evidence from observational studies and clinical trials has associated gut microbiota with infectious diseases. However, the causal relationship between gut microbiota and infectious diseases remains unclear.We identified gut microbiota based on phylum, class, order, family, and genus classifications, and obtained infectious disease datasets from the IEU OpenGWAS database. The two-sample Mendelian Randomization (MR) analysis was then performed to determine whether the gut microbiota were causally associated with different infectious diseases. In addition, we performed reverse MR analysis to test for causality.Results: Herein, we characterized causal relationships between genetic predispositions in the gut microbiota and nine infectious diseases. 8 strong associations were found between genetic predisposition in the gut microbiota and infectious diseases. Specifically, the abundance of class Coriobacteriia, order Coriobacteriales and family Coriobacteriaceae was found to be positively associated with the risk of Lower Respiratory Tract Infections (LRTI). On the other hand, family Acidaminococcaceae, genus Clostridiumsensustricto1 and class Bacilli were positively associated with the risk of endocarditis, cellulitis, and osteomyelitis, respectively. We also discovered that the abundance of class Lentisphaeria and order Victivallales lowered the risk of sepsis.Through MR analysis, we found that gut microbiota were causally associated with infectious diseases. This finding offers new insights into the microbe-mediated infection mechanisms for further clinical research.